A socioeconomic analysis of commuting professionals - Moritz Kersting; Eike Matthies; Jörg Lahner; Jan Schlüter (Transportation, 2020)
Everyday commuting as a mobility phenomenon is well-investigated and has been the topic of many contributions. Nevertheless, the distinct determinants of the commuting professional's motivation to regularly travel comparably long distances have not been in the focus of research yet. Thus, this contribution analyses the sociodemographic variables that underpin the well-educated group's decision to commute longer distances than other educational groups. For German Microcensus data, ordered logistic regression models are used to estimate and compare the influences of sociodemographic variables on all commuting employees and commuting professionals. The data of German Microcensus of the year 2012 are used for the analysis. The results imply that some characteristics exert the already known effects on both samples. Others do vary with education and thus illustrate some unique sociodemographic influences on the commuting behaviour of professionals.
Keywords: 380; Commuting; Professionals; Education; Occupation; Microcensus; Germany